2022
DOI: 10.1021/jacs.2c02173
|View full text |Cite
|
Sign up to set email alerts
|

Fused-Ring-Linked Covalent Organic Frameworks

Abstract: The development of linkage chemistry in the research area of covalent organic frameworks (COFs) is fundamentally important for creating robust structures with high crystallinity and diversified functionality. We reach herein a new level of complexity and controllability in linkage chemistry by achieving the first synthesis of fused-ring-linked COFs. A series of bicyclic pyrano [4,3-b]pyridine COFs have been constructed via a cascade protocol involving Schiffbase condensation, intramolecular [4 + 2] cycloadditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 91 publications
1
36
0
1
Order By: Relevance
“…Of note, the metallophthalocyanine-COFs with 5th and 6th period metals (e.g., Pt, Rh, Ag, W, Ta, Mo, Os, and Re) have been predicted based on first-principles density functional theory calculations, 223 but their synthesis still remains blank. 3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluorophthalocyanines under alkaline conditions (Fig. 6).…”
Section: Review Articlementioning
confidence: 96%
See 3 more Smart Citations
“…Of note, the metallophthalocyanine-COFs with 5th and 6th period metals (e.g., Pt, Rh, Ag, W, Ta, Mo, Os, and Re) have been predicted based on first-principles density functional theory calculations, 223 but their synthesis still remains blank. 3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluorophthalocyanines under alkaline conditions (Fig. 6).…”
Section: Review Articlementioning
confidence: 96%
“…218 In addition to the pyrazine-linked COFs, the piperazinelinked phthalocyanine-COF has also been reported by Huang and co-workers. By Buchwald-Hartwig cross-coupling reaction of nickel(II) 2,3,9,10,16,17,23,24-octaaminophthalocyanine and cobalt(II) 1,2,3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluorophthalocyanine under solvothermal conditions (dioxane, triethylamine, 120 1C), the piperazine-linked heterometallic NiPc-NH-CoPcF 8 COF was generated. 219 NiPc-NH-CoPcF 8 crystallized in the tetragonal P4/mmm space group, with AA stacking mode, a pore size of 1.1 nm, and an interlayer spacing of 3.6 Å.…”
Section: Review Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Since the groundbreaking research on covalent organic frameworks (COFs) reported by Yaghi et al, such type of popular crystalline materials have attracted extensive attention. COFs are constructed from organic ligands through covalent bonds and possess predesigned structures as well as precise customized functions that facilitate the implementation of chemical and structural control. Despite enormous attractive research on the design and construction of COFs having been conducted for nearly 20 years, there is still great potential for the development of luminescent COF materials. Notably, the natural π-conjugated structure of COFs is beneficial to study their luminescence performance, while the π–π stacked structure also causes aggregation-induced quenching (ACQ) and hinders the emission of COFs. , Meanwhile, weakening the stacking degree between layers will increase the intramolecular rotation, which is also a dilemma for luminescence. At present, fluorescent organic linkers with large conjugated structures or with an aggregation-induced luminescence effect are usually selected for the fabrication of luminescent COFs. Emissive COFs can also be obtained via postmodification or exfoliation. To improve the luminescence properties of COFs in an effective way, the emergence of luminescent composites based on COFs stands out from single COFs. As we know, even though luminescent COFs as emerging functional materials have been dramatically studied over the past few years, ,, research on directly growing COFs on the core substrate with a limited number of layers to improve the luminous efficiency still remains less understood.…”
Section: Introductionmentioning
confidence: 99%